Awareness, knowledge, and attitudes of the Belgian general population towards paternal perinatal depression: a descriptive cross-sectional study - Akalin, Ayse; D’haenens, Florence; Tricas-Sauras, Sandra; Vermeulen, Joeri; Demedts, Dennis; Buyl, Ronald; Fobelets, Maaike (Frontiers in Psychiatry, 2025)
BackgroundPaternal perinatal depression affects 10% of fathers, implying a significant burden on families and public health. A better insight into the population’s health literacy could guide professionals and policymakers in addressing these men and making better use of existing healthcare options. It is also crucial for caregivers, as they play a vital role in identifying symptoms, encouraging help-seeking, and reducing stigma. This study aimed to explore the awareness, knowledge, and attitudes of the general population in Belgium towards paternal perinatal depression, using the validated DDads (Depression in Dads) questionnaire.MethodsThis descriptive, cross-sectional study was conducted between March and May 2020-2022 using convenience sampling. Participants aged over 18 years, with a good understanding of Dutch and residing in the Brussels-Capital Region or Flemish Brabant were invited to participate. Data were analysed using descriptive statistics, Chi² analysis, and independent sample t-test.ResultsA total of 314 participants, including women (n=165) and men (n=149) completed the questionnaire. Anxiousness was the most frequently cited mental health problem for men during their partners’ pregnancy (82.5%) and in the postnatal period (68.5%). Over one-third (37.3%) viewed paternal depression as a ‘normal’ part of the transition to fatherhood. The recommended treatment for paternal depression was mostly non-pharmacological, with family support ranking first (79.9%) and seeking support from informal networks being the most recommended approach (45.2%). New personality characteristics such as withdrawal, cynicism, raging attacks, and irritability, among others, were seen as common symptoms (64.6%). Although 70% of respondents believed that perinatal depression requires specialized treatment, only 39.2% agreed that all men should be screened for depression during pregnancy.ConclusionsRecognition of paternal depression symptoms was relatively low but higher among females, participants with higher education, and those aware of paternal depression. Professional support recommendations were limited, especially among young people and those without children. The terms ‘paternal perinatal depression’ and ‘perinatal mental health’ are poorly understood. The findings highlight critical gaps in awareness and attitudes, offering valuable insights. Future research should develop tailored interventions to support men’s mental well-being during the perinatal period. Targeted awareness campaigns and healthcare improvements are crucial for addressing this issue.